Penyuluhan Upaya Pencegahan Bullying pada Anak di SMP Negeri 1 Bangunrejo - Hendratama, Ozi; Jaya, Wayan Satria; Febrianti, Aurora Nandia; Ramadani, Alensi; Karyono, Dhani (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The purpose of this PKM program is to increase students' understanding of the meaning, forms, and impacts of bullying, provide students with skills in preventing and overcoming bullying, foster empathy, tolerance, and mutual respect among students, reduce the potential for bullying cases in schools and assist schools in creating a safe, comfortable, and conducive learning environment. This counseling uses interactive lectures, group discussions, role-playing simulations and evaluations. The target audience for this counseling is all students at SMP Negeri 1 Bangunrejo. The success rate of this counseling is seen from 85% of students understanding the definition and types of bullying after the counseling, 78% of students being able to identify the impacts of bullying, and 80% of students being able to formulate steps to prevent bullying in schools. This indicates that the counseling is effective in increasing student awareness and creating a healthier school environment.